Professional development and succession planning in organizations - Kumar, Chowlam Sandeep (The journal of contemporary issues in business and government, 2020)
Professional development and succession planning should ensure the institution's workers' passion, as well as provide organizations with the opportunity to expand their professional talents, provide them with a work perspective, and increase the attraction of joining the business. The purpose of corporate succession planning is to guarantee that the company has sufficient personnel resources to meet its long-term goals for a few employments. It is increasingly essential to be able to readily alter paths in one's profession. Professionals' workspaces are in jeopardy owing to organizational changes, the company's existence, organization and the workers, insolvency, and so on; therefore, they must take responsibility for their professional growth.